Reflections on the Evolution of Operations Management - Graves, Stephen C. (Management Science, 2021)
In this paper, I provide some observations on how the academic field of operations management has changed over the past 40 years. For this purpose, I have identified and classified the operations management (OM) papers published in Management Science in 1976 and in 2016. From this review, I comment on what’s changed, what’s new, and what we might see in the future. In reflecting on these changes, I also document and discuss how the OM editorial structure and mission have evolved at Management Science over this time. This paper was accepted by David Simchi-Levi, Special Section of Management Science: 65th Anniversary.